OVEN DESTILATOR PENGOLAH SAMPAH PLASTIK RAMAH LINGKUNGAN “Pemanfaatan Asap Cair Hasil Olahan Oven Destilator untuk Pengawetan Kayu - Ganefati, Sri Puji; Hendrarini, Lilik; Windarso, Sarjito Eko (Jurnal Teknologi Lingkungan, 2011)
Up to now, the majority of people treat plastic waste by burning and disposing it directly to the surrounding environment. The burning of the waste causes air pollution due to toxic compound called dioxin which is harmful for human health. Meanwhile, the dumping of plastic waste into water bodies can causing some negative effects such as the clogging of water duct or river which may lead to flooding. Annually, the number of plastic bag used can reach 500 million – 1 billion, which is equal to 10 fold wrapping of earth surface (Nitizen, 2008). The best handling of plastic waste are using reuse or recycle methods which are environmentally friendly and at the same time can gain economical value1). The study is aimed to: 1) understand the capability of oven distillator in processing plastic waste into plastic grain and liquid smoke, 2) understand the influence of liquid smoke towards wood durability, 3) understand the price of the oven distillator and the corresponding break even point (BEP).The study was an experimental one and employed pre test and post test with control group design, and simultaneously assessing equipment’s production capacity. The data was analyzed descriptively and analytically with Anova test and t-test at 95% level of significance.The results show that oven distillator capable for processing 97,3% of plastic waste into plastic grain, while the rest was converted into liquid smoke. The liquid smoke was proved affect wood preservation (anova test, p<0.001), and have similar quality compared with varnish use (t-test, p=0,764). The cost analysis shows that the distillatory raise economical value of the waste by 217,66%, and The BEP would be reached in 68 days if 12 kg plastic is processed daily. It is advised that he oven can be used by general community or home industries for applying green and high economically value of plastic waste processing.